American heroes ebook - Patterson, James (2024)
Instant #1 National Bestseller! “A monumental contribution to comprehending the motivation and distinguished service of American warriors.  American Heroes  is a book that every citizen should read.” — Association of the United States Army From the authors of  Walk in My Combat Boots,   “American Heroes  is a gripping collection of firsthand accounts…capturing the indomitable spirit of our nation’s finest” (Jack Carr, #1  New York Times  bestselling author of The Terminal List series). U.S. soldiers who served in overseas conflicts—from World War II, Korea, and Vietnam to Iraq and Afghanistan—share true stories of the actions that earned them some of America’s most distinguished military medals, up to and including the Medal of Honor.    They never acted alone, but always in the spirit of camaraderie, patriotism, and for the good of our beloved country.     There has never been a better time for all of us to think about duty, sacrifice, and what it means to be an American hero.